The Role of Legal Opinion as Legal Problem Solving Method - Herowati Poesoko; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum, Universitas Warmadewa, 2020)
This study aims to describe Legal Opinion as a Legal Problem Solving Method. The method used in this study is normative legal research; meanwhile the approach used in this study is legal research method. The results revealed that firstly based on legal issues which certainly cannot be separated from the field of law to be studied, while the preparation of legal opinions depends on the depth of knowledge of the legal field what will be found, it is seen in the analysis used in order to find legal problem solving that can be prescription of the legal issue. Therefore, the role of legal opinion in the structure of the layer of legal science can be useful as a method in developing practical law or in developing theoretical law.